2015
DOI: 10.5194/acp-15-2709-2015
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for tropospheric wind shear excitation of high-phase-speed gravity waves reaching the mesosphere using the ray-tracing technique

Abstract: Abstract. Sources and propagation characteristics of highfrequency gravity waves observed in the mesosphere using airglow emissions from Gadanki (13.5 • N, 79.2 • E) and Hyderabad (17.5 • N, 78.5 • E) are investigated using reverse ray tracing. Wave amplitudes are also traced back, including both radiative and diffusive damping. The ray tracing is performed using background temperature and wind data obtained from the MSISE-90 and HWM-07 models, respectively. For the Gadanki region, the suitability of these mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 59 publications
1
57
1
Order By: Relevance
“…The features seen in the observed zonal winds are reproduced in the model winds shown in Figure 4 b, except the presence of TEJ and descending easterlies in the mesosphere during March-May. There are reports about the climatological monthly mean structure of zonal and meridional winds obtained over Gadanki region using a variety of instruments 32 , which agree well with our present observations over Thiruvananthapuram.…”
Section: Time Height Section Of Climatological Mean Horizontal Winds supporting
confidence: 82%
See 1 more Smart Citation
“…The features seen in the observed zonal winds are reproduced in the model winds shown in Figure 4 b, except the presence of TEJ and descending easterlies in the mesosphere during March-May. There are reports about the climatological monthly mean structure of zonal and meridional winds obtained over Gadanki region using a variety of instruments 32 , which agree well with our present observations over Thiruvananthapuram.…”
Section: Time Height Section Of Climatological Mean Horizontal Winds supporting
confidence: 82%
“…The zonal wind observations in the 70-80 km height range over the Indian region provided by rocketsonde HRDI/UARS, and MST radar during 1977-2010 showed a decreasing trend of 2 m/s/year changing from strong eastward winds to weak westward winds in recent years 31 . Pramitha et al 32 also reported climatological monthly mean contours of temperature, zonal wind and meridional wind obtained over Gadanki region combining a variety of instruments.…”
mentioning
confidence: 99%
“…However, there are also indications from radiosonde and ground-based measurements (e.g. Leena et al, 2012;Pramitha et al, 2015) and modeling (e.g. Preusse et al, 2014) that in the regions of deep convection GWs are excited around tropopause altitude.…”
Section: Zonal Average Of Convective Gwmf and Its Vertical Gradientsmentioning
confidence: 99%
“…Previous studies have shown that GROGRAT is an efficient tool to identify GW sources (Guest et al, 2000(Guest et al, , 2002Pramitha et al, 2015) and to simulate GW-background interactions such as GW effects, wave filtering, space and time variability of GW activity and characteristics (Wei and Zhang, 2015). For example, GROGRAT simulations help to interpret global GW observed morphology derived from satellite observations .…”
Section: Ray Tracingmentioning
confidence: 99%